Share pledges and firm value - Li, Michelle; Liu, Chelsea; Scott, Tom (Pacific-Basin finance journal, 2019)
Share pledging is when shareholdings are used as collateral to obtain loans. While uncommon in many developed economies, the practice is prevalent in the Chinese capital markets. Using a sample of Chinese listed firms over 2003–2015, we find a positive association between share pledges by the largest shareholder and firm value. To alleviate concerns around the robustness of our results, we examine the relationship between share pledging and firm value using the Heckman selection model, a difference-in-differences model, change models, and employ other additional tests. Further, we examine stock price crash risk for the pledged firms and find no evidence of any increase in crash risk, which may partially explain the positive association between share pledging and firm value. Our results provide insights into the controversial practice of share pledging in the developing market of China. •Share pledging uses shareholdings as collateral for loans and is common in some countries.•Using Chinese data we find that share pledges by the largest shareholder of a firm are positively associated with firm value.•We run tests to alleviate concerns around potential endogeneity and find consistent results.•We find no association between shares pledges and stock price crash risk.